HUBUNGAN MOTIVASI BELAJAR, DISIPLIN BELAJAR, DAN AKTIVITAS BELAJAR DENGAN HASIL BELAJAR DALAM PEMBELAJARAN TEMATIK - Nabilah, Hariani Nisa; Asrori, Muhammad; Sulistyarini, Sulistyarini (Jurnal Visi Ilmu Pendidikan, 2023)
This study aims to describe the relationship between in learning motivation, learning discipline, and learning activity with the students learning achievement in the thematic lesson. This study used a quantitative approach with correlation research type. The sample of this amounted to 27 students. Data collection was carried out using a questionnaire and documentation study. The analysis technique was carried out by using determine the relationship between in learning motivation, learning discipline, and learning activity on the students"™s learning achievement using simple correlation analysis and multiple correlation. The results showed that there was a relationship between (1) learning motivation with the students learning achievement of 0,239 categorized as "low", (2) learning discipline with the students learning achievement of 0,315 categorized as "low", (3) learning activity with the students learning achievement of 0,310 categorized as "low", (4) learning motivation and learning discipline with the students learning achievement of 0,337 are categorized as "low", (5) learning motivation and learning activity with the students learning achievement of 0,384 are categorized as "low", (6) learning discipline and learning activity with the students learning achievement of 0,340 are categorized as "low", (7) learning motivation, learning discipline, and learning activity with the students learning achievement of 0,399 are categorized as "low".  Keywords: Learning Motivation, Learning Discipline, Learning Activity, Students"™ Learning Achievement in the Thematic Lesson